My Life, My Story and Life Recovery among Veterans with Substance Use Problems - Grace Chang; Martha Duffy; Susan Nathan (Patient Experience Journal)
Objective: The United States Veterans Health Administration My Life, My Story (MLMS) program is a patient-centered care intervention where veterans are interviewed about their life story and may grant permission to include it in their electronic health record (EHR). Our purpose was to focus on a sample of MLMS narratives from veterans with self-disclosed substance use (SU) from our institution, and to evaluate the potential relationship between their content and a life change for the better, and to compare their content with the EHR. Methods: The narratives were reviewed on 4 domains (past challenge, substance use, experience of a turning point or insight, life improvement) by two reviewers using a pre-specified code book. 31 narratives were reviewed. Additional demographic and clinical data were abstracted from the EHR. Results: Veterans' mean age was 68.7 (SD = 6.0) years when interviewed. All were male and had a tobacco (23%), SU (45%), anxiety (32%), mood (45%), or post-traumatic stress (32%) problem on EHR review. 48% received outpatient mental health treatment whereas 24% received outpatient SU treatment. With regards to MLMS content, 74.2% described a significant life stressor, 93% confirmed SU, 71% reported a turning point, and 80.7% had experienced life improvement. There were no statistically significant relationships between the EHR data and MLMS content areas. However, when a turning point was described, the odds of having a life improvement were increased 26-fold (OR = 26.2, 95% CI = 2.4, 288.9, c-statistic = 0.84). Conclusion: The MLMS narrative from the veterans' perspective provides additional richness to their history unavailable in the EHR.